2008
DOI: 10.2341/07-95
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Restorative Materials and Opposing Enamel Wear

Abstract: The data obtained in this study can help practitioners with selection of the appropriate restorative materials to minimize further tooth and restoration wear, which is an important consideration during treatment planning. SUMMARYThis in vitro study compared the effects of a gold alloy (Degulor M), four dental ceramics (IPS Empress, IPS Empress 2, Duceram Plus, Duceram LFC) and a laboratory-processed composite (Targis) on the wear of human enamel. The amount of wear of the enamel (dental cusps) and restorative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It was noticeable that polished areas are visible only on enamel/steatite opposing zirconia ceramics. After wear tests with porcelain, provoked wear [29] and ploughing on the antagonist surface could be determined. SEM pictures on porcelain specimens revealed circular defects, which are supposed to be abraded cone cracks [30].…”
Section: Discussionmentioning
confidence: 99%
“…It was noticeable that polished areas are visible only on enamel/steatite opposing zirconia ceramics. After wear tests with porcelain, provoked wear [29] and ploughing on the antagonist surface could be determined. SEM pictures on porcelain specimens revealed circular defects, which are supposed to be abraded cone cracks [30].…”
Section: Discussionmentioning
confidence: 99%
“…The higher standard deviations in this group affirm this assumption. Other studies have, furthermore, shown that ceramics or ceramic veneers cause greater wear of opposing dentition than composite materials 5,6) . This is an advantage of composite restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides good chemical properties and low wear, the esthetics of ceramics are excellent. In contrast, some disadvantages such as abrasiveness to opposing tooth structures [4][5][6] , chipping behavior 7) , invasive preparation design and costs have been reported. Resin composite restorations might be an alternative which is able to overcome those disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Even though the mechanical and optical properties of the ceramic materials are important, many variables may contribute to the predictability and clinical longevity of all-ceramic restorations, including the adhesive and luting system used, the curing mechanism, the light-curing unit, and the microstructure and thickness of the ceramic. 3 Resin cements are necessary to bond porcelain and glass-ceramic resto-…”
Section: Introductionmentioning
confidence: 99%